BORN TO BE SOVIET: AMANGELDY IMANOV’S LIFE AFTER DEATH THROUGH THE PRISM OF THE SOVIET NATIONALITIES POLICY - Zhaneken, Adel (School of Sciences and Humanities, 2023)
There is growing interest in historical studies in deconstructing Soviet narratives about national heroes. Scholars studying Soviet-era Kazakhstan agree that the image of Amangeldy Imanov was carefully crafted by Soviet actors . However, the Soviet narrative about Amangeldy fluctuated, which suggests that it was shaped by political and ideological shifts. To explore the shifts in Soviet policies that affected the development of the narrative about Amangeldy, I conducted archival research in Almaty . I analyzed sources that mention Amangeldy, which were compiled in the Soviet Union (SU) between the 1920s and 1945, such as propaganda articles, history textbooks, interviews with people who knew Amangeldy, the Soviet film Amangeldy, and wartime newspapers. The image of Amangeldy reflected the dynamics of the Soviet nationalities policy. The evolution of the narrative occurred in stages that built on each other, leading up to an accumulative status of a national hero. The first mentions of Amangeldy emerged during the period of Korenizatsiia in the 1920s, which involved the incorporation of local history into broader history of the SU. The second stage unfolded in the 1930s at a time when the Friendship of the Peoples policy sought to elevate the role of the Russian nation. Political literature and film emphasized the class identity of the hero. Amangeldy became the personification of the 1916 uprising and a Bolshevik. The third stage coincides with the war. Wartime propaganda lionized Amangeldy into an epitome of the “Kazakh fighting traditions.” Overall, the study demonstrates the importance of critically re-examining the Soviet legacy in Kazakh national hero narratives like Amangeldy’s.
Keywords: type of access: open access; Amangeldy Imanov; soviet nationalities policy